2000 years of Christ's power ; pt 1 - Needham, Nick R. (London, UK Grace, 1997)
Contents : part 1 : The age of the early church fathers. Includes bibliographical references and index.
Keywords: Church history -- primitive and early church, ca. 30 - 600.